Manifestation of the Ecosystem Learning Model for Biodiversity to Improve Competency-Based Environmental Education - Sugiarto, Slamet Widodo; Imran, Zulhamsyah; Perdinan; Widayanti, Sri; A, Trijanti A. Widinni; Widiastuti, Herni; Rahmawati, Dewi (SEAMEO BIOTROP, 2023)
Integrating environmental education and increasing competency through the development program of educational ecosystem models and biodiversity education and learning ecosystems can effectively enrich materials and practices to increase students' knowledge, understanding, and skills. The embodiment of the Sensory Garden and Therapeutic Garden prototypes as natural laboratories and libraries will be an effective and adaptive way of developing competency[1]based education and learning models as well as the interests and talents of students.